The Temporal Association Between Simultaneous Alcohol and Cannabis Use and High-Risk Sexual Behaviors - (:unkn) unknown (My University, 2023)
High-risk sexual behaviors (HRSBs; e.g., having sex without protection against pregnancy or sexually transmitted infections) are a public health problem. HRSBs disproportionally impact college students and are associated with numerous negative outcomes, such as unwanted pregnancies. Alcohol use has been strongly linked to HRSBs in college students, but the research is less clear when investigating the relationship between cannabis use and HRSBs. Additionally, there is a lack of research examining the relationship between simultaneous alcohol and cannabis (i.e., marijuana or SAM) use (i.e., using alcohol and cannabis at the same time so that the effects overlap) and HRSBs in college students. Thus, the current study aimed to examine this relationship temporally utilizing a 30-day daily diary design in alcohol and cannabis using college students. Participants (N = 103) completed brief, daily surveys for 30 consecutive days measuring their SAM use and HRSBs. Moderators, including sex-related SAM expectancies and impulsivity, of this relationship were also investigated. Results indicated no significant associations between SAM use and HRSBs. No significant two-way interactions between sex-related SAM expectancies or positive urgency were found. A significant association between positive urgency and HRSBs was observed, such that as positive urgency decreased, participants had lower odds of engaging in HRSBs. When accounting for negative urgency, SAM use was significantly related to HRSBs, such that not engaging in SAM use decreased the likelihood of engaging in HRSBs. Further, results suggested evidence for a significant two-way interaction between SAM use and sensation seeking. Specifically, for participants high in sensation seeking, relative to low, the odds of engaging in HRSBs decreased for those participants that did not engage in SAM use, compared to those that did in engage in SAM use. Significant associations between age, such that as age increased, the odds of engaging in HRSBs increased, and sex assigned at birth, such that males were at lower odds of engaging in HRSBs than females, were also observed. Results need additional replication to confirm findings, but may suggest a need to target older, female students, positive urgency, and negative urgency to reduce HRSBs.